(untitled) (Annals of Medical Research, 2021)
Aim: Early prediction of acute kidney injury in multiple trauma patients to decrease its sequel and begin early treatment to improve outcome. Acute kidney injury (AKI) is an uncommon but serious complication after trauma. In large trauma victims, the incidence of post-traumatic AKI varies from 0.098 to 8.4% in published series with mortality ranging from 7 to 83%.Patients who develop AKI have a high mortality rate, especially when requiring dialysis with rates ranging from 37% to 88%. There has been progressive technical and scientific development in patient care towards AKI prevention.Material and Methods: This study is prospective study conducted in emergency department (ED) and randomly selected 270 multiple trauma patients at Suez Canal university hospital from them 21 patients developed acute kidney injury. And select according the Inclusion criteria and exclusion criteria.Results: All included 270 patients with multiple trauma 21 (7.7%) developed AKI and 3 (1.1%) of them required dialysis with mortality rate of (38%). 88.50% of multiple trauma patients were suffering from head trauma and (50.30%) were having abdominal injury while 36.80% were suffering from orthopedic trauma. And patients were developed AKI divided into 3 stages; stage one (5.20%), stage two (1.50%), and stage three (1.10%). Conclusion: Majority of studied patients were have normal creatinine level at time of arrival, after 24hrs some patients developed acute kidney injury and the most common cause was hypovolemic shock while the most common cause of mortality in acute kidney injury was septic shock.